Comparison of Post-Operative Surgical Site Infection in Uncomplicated Laparoscopic Cholecystectomies in Patients Who Received Post-Operative Antibiotics versus Patients who did not Receive Post-Operative Antibiotics; A Comparative Study - Naeem, Umer; Hussain, Syed Mukarram; Yousaf, Muhammad Danial; Saqlain, Muhammad; Imran, Muhammad; Hassan , Najm Ul (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the frequency of post-op “surgical site infection” in uncomplicated laparoscopic cholecystectomies in patients who received post-op antibiotics versus those who did not.Study Design: Quasi-experimental studyPlace and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi, Pakistan from Jun 2022 to May 2023.Methodology: A total of 342 patients [171 in the Antibiotics-Group and 171 in the No-Antibiotics-Group] fulfilling the inclusion criteria who underwent uneventful laparoscopic cholecystectomy were included in the study. In all these patients, baseline characteristics were documented. Patients in Group-A were given antibiotic therapy post-operatively, while patients in Group-B were not given antibiotics after the operation. Patients in both groups were followed up on day 10 after the surgery to assess for “surgical site infection.Results: In our study, the mean age of the study population was 38.41±10.12 years. There were 127(37.13%) male participants, while 215(62.87%) participants were female. The mean body mass index (BMI) was 31.14±4.49 kg/m2. Composite frequency of “surgical site infection” was 38(11.10%). In patients who were given post-op antibiotics, the frequency of “surgical site infection” was 16(9.35%), while in patients who did not receive any antibiotics after the surgery, the frequency of “surgical site infection” was 22(12.86%), (p=0.302).Conclusion: Antibiotic therapy should be reserved for patients who develop “surgical site infection” instead of being used in all patients.